Analisis Karakteristik Champion Desa Wisata Di Pulau Lombok - Akhmad Saufi; Hermanto Hermanto; Diswandi Diswandi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
The roles of local champions in the development of tourism villages are central as they can act as agents of change as well as motivators for community participation in tourism development. This study aims to analyze the characteristics of the local champions in tourism villages. Data was collected from four tourism villages on Lombok Island. Interviews were conducted with seven informants who play roles as local champions in the tourism villages. The results of the interviews were transcribed and analyzed using the content analysis approach. The research found four main characteristics of a local champion, namely visioning, affiliating, altruistic and autonomous, which inspire a local champion to initiate a tourism business and motivate his/her communities to participate in the development of a tourism village. Providing training and mentoring to his/her community members, and having an orientation towards the sharing benefits and development are two bold characteristics that distinguish a local champion from an entrepreneur in general.This study provides recommendations for local government and other related institutions regarding appropriate approach and mechanisms in order to help stimulate the emergence of local champions in the tourism villages